Panarchy and the Law - J. B. Ruhl (Ecology and Society, 2012)
Panarchy theory focuses on improving theories of change in natural and social systems to improve the design of policy responses. Its central thesis is that successfully working with the dynamic forces of complex adaptive natural and social systems demands an active adaptive management regime that eschews optimization approaches that seek stability. This is a new approach to resources management, and yet no new theory of how to do things in environmental and natural resources management, particularly one challenging entrenched ways of doing things and the interests aligned around them, is likely to gain traction in practice if it cannot gain traction in the form of endorsement and implementation through specific laws and regulations. At some point, that bridge must be crossed or the enterprise of putting panarchy theory into panarchy practice will stall. Any effort to operationalize panarchy theory through law thus comes up against the mission of law to provide social stability and the nature of law itself as a complex adaptive system. To state the problem in another way, putting panarchy theory into practice will require adaptively managing the complex adaptive legal system to adaptively manage other complex adaptive natural and social systems, all in a way that maintains some level of social order. Panarchy theorists have yet to develop an agenda for doing so. It is time for lawyers to join the team.